Sandwich-type architecture film based on WS2 and ultrafast self-expanded and reduced graphene oxide in a Li-ion battery - Wenelska, Karolina; Kędzierski, Tomasz; Bęben, Damian; Mijowska, Ewa (Frontiers in Chemistry, 2023)
Graphene, since its discovery, has been widely considered as a great material that pushed forward the Li-ion battery (LIB) field and brought a development in its performance. However, most of current graphene related research is focused on graphene-based composites as electrode materials, highlighting the role of graphene in the composite materials. Here, we focused on three-dimensional composite film with unique sandwich-type architecture based on the ultrafast self-expanded and reduced graphene oxide (userGO) and exfoliated WS2. What is worth highlighting, this strategy serves the non-active agents (e.g. carbon black and poly (vinylidene fluoride)) free electrode in LIBs in the form of film. Interestingly, the ultra-quick exothermal nature of the USER reaction allows the internally generated gases being rapidly released to create highly porous channels inside the film. Hence, improvement of Li ions transport in LIBs boosted the electrochemical performance of both film components: ex-WS2 and reduced graphene. It resulted in high specific capacity of 762 mAh/g at 0.05 A/g and high Coulumbic efficiency (101%) after 1000 cycles. In overall, the presence of userGO induces the highest capacity at low current and ex-WS2 allows to keep higher reversible capacity. It clearly shows that expanded graphene layer is an excellent shield of ex-WS2 protecting against pulverization promoting both stability and capacity.